2022
DOI: 10.1101/2022.03.31.486401
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Toxicity of extracellular alpha-synuclein is independent of intracellular alpha-synuclein

Abstract: Parkinson′s disease (PD) pathology progresses throughout the nervous system affecting numerous neuronal structures. It has been postulated that the progression of the pathology is based on a prion-like disease mechanism partly due to the seeding effect of endocytosed alpha-synuclein (ASYN) on endogenous ASYN. The appearance of the pathology in dopaminergic neurons leads to neuronal cell death and motor symptoms. However, the effect on other neuronal structures is more inconsistent, leading to a higher variabil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
0
0
Order By: Relevance
“…Once internalized by recipient cells, aSyn aggregates may induce the misfolding and aggregation of intracellular aSyn, thus perpetuating the cycle of aggregate formation (Masuda-Suzukake et al, 2013;Paumier et al, 2015). Experiments using aSyn KO mice showed that endogenous aSyn is essential for the spreading of pathology, a process that does not require aSyn toxicity (Dening et al, 2022). Consequently, transmitting aSyn aggregates between cells may contribute to the progression of neurodegeneration observed in PD and related disorders.…”
Section: Synucleinopathies As Prion-like Diseasesmentioning
confidence: 99%
“…Once internalized by recipient cells, aSyn aggregates may induce the misfolding and aggregation of intracellular aSyn, thus perpetuating the cycle of aggregate formation (Masuda-Suzukake et al, 2013;Paumier et al, 2015). Experiments using aSyn KO mice showed that endogenous aSyn is essential for the spreading of pathology, a process that does not require aSyn toxicity (Dening et al, 2022). Consequently, transmitting aSyn aggregates between cells may contribute to the progression of neurodegeneration observed in PD and related disorders.…”
Section: Synucleinopathies As Prion-like Diseasesmentioning
confidence: 99%